The complete mitochondrial DNA of Ancherythroculter wangi. Issue 1 (2nd January 2018) - Yan, Taiming; Wang, Xiongyan; Zhang, Songpei; He, Liang; He, Zhi
Abstract: The complete mitochondrial genome of Ancherythroculter wangi was determined. The mitochondrial genome, consisting of 16, 622 base pairs (bp), encoded 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs and a non-coding control region, as those found in other Ancherythroculter species. These results can provide useful data for further studies on taxonomic status, molecular systematics, and stock evaluation.